2012
DOI: 10.1590/s0004-27492012000100016
|View full text |Cite
|
Sign up to set email alerts
|

New approaches and potential treatments for dry age-related macular degeneration

Abstract: Emerging treatments for dry age-related macular degeneration (AMD) and geogra phic atrophy focus on two strategies that target components involved in physiopathologi cal pathways: prevention of photoreceptors and retinal pigment epithe lium loss (neuro protection induction, oxidative damage prevention, and visual cycle mo dification) and suppression of inflammation. Neuroprotective drugs, such as ci liary neurotrophic factor, brimonidine tartrate, tandospirone, and anti-amyloid β antibodies, aim to prevent apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…6 Although a number of agents are available to treat exudative ('wet') AMD, prevention of the disease continues to be more challenging. 8,9 The pathogenesis of AMD remains indeterminate and is likely to be multifactorial. 10 The disease is related to well-known risk factors, such as cigarette smoking, elevated serum cholesterol levels, and hypertension, that are shared with atherosclerosis and consequently with increased risk of cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…6 Although a number of agents are available to treat exudative ('wet') AMD, prevention of the disease continues to be more challenging. 8,9 The pathogenesis of AMD remains indeterminate and is likely to be multifactorial. 10 The disease is related to well-known risk factors, such as cigarette smoking, elevated serum cholesterol levels, and hypertension, that are shared with atherosclerosis and consequently with increased risk of cardiovascular disease (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10-18% of individuals between 65 and 75 years old have lost some central vision as a result of AMD (5,12,14). Although neovascular AMD is the most damaging form of the disease, atrophic AMD accounts for approximately 90% of all cases (reviewed in (15)). …”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, a significant amount of research has been focused on the physiopathology of atrophic AMD and new treatment approaches. However, research has been hampered by some issues, such as the multifactorial nature of atrophic AMD, its complex physiopathology, the lack of a suitable animal model, and the lack of in vitro systems for testing new drugs (reviewed in (15)). Currently, the only approved treatment for atrophic AMD is the use of the Age Related Eye Disease Study formulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies show that oxidative stress is the important factor for ARMD progression. 18 It has been shown that ARMD affects the macula, the posterior aspect of the retina responsible for central visual acuity. 4 The retina is an ideal environment for the generation of ROS for several reasons.…”
mentioning
confidence: 99%